The role of chemokines in ocular diseases. Part. I. Structure and role of chemokines in chosen diseases - Malesiński, Roman; Mrugacz, Małgorzata; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
The chemokines are a large family of chemotactic cytokines produced by leucocytes, fibroblasts, keratynocytes and the others tissue cells. Chemokines stimulate and regulate leucocytes migration in inflammations. All the described human chemokines transmit intracellular signals by binding and activating specific G protein-coupled receptors on the cell surfaces of their target cells. Chemokines are involved in variety of inflammatory and autoimmune diseases.